O mal-estar discente numa escola do outro século: olhares de alunos - Baptista, Carla (2018)
This communication is based on the purpose of trying to understand the perceptions and experiences of students with a high level of academic success, about the meaning of their education process. it is, therefore, an exploratory, descriptive and interpretive study within the qualitative paradigm intending to portray students’ vision and school experiences. this research discusses the challenges that schools are currently facing through the voice of the students. the data was collected in an urban high school in the center of oporto, from twenty and one students (three groups of seven students - 9th, 10th and 12th grade), during the third term of 2014/2015 school year, using the focus group research technique. the collected and analyzed data in this study, although it may not be generalizable, allow us to conclude that, in the studied case, the process of schooling reveals serious shortcomings in its course and it is perceived a lack of direction in school practices experienced by students. the students reveal a vision of a school grammar that should no longer exist, which marks negatively their school experience in the dimensions related to the lesson, to the assessment and to the teacher. regarding the school as socializing locus, the view is more positive.